An Exploratory Study of Asset Liability Management in the Insurance Industry in Nigeria: A Panel Approach - Olowokudejo, Folake; Akindipe, Oluwaleke Ebenezer (Acta Universitatis Danubius. Œconomica, 2022)
Asset Liability Management’s main goal is to manage risk, not eliminate it, in order to reduce net interest income volatility in the short term and safeguard the organization’s economic worth over the long term. This study looked at certain best practices in asset-liability management and how they affected the performance of the insurance business between 2011 and 2021 while taking into consideration the particular characteristics of the Nigerian economy. Data on total corporate assets, shareholder’s funds, and profit after tax for the time period were taken from the annual reports and digest of the Nigerian Insurers Association (NIA). The results of the data’s stationarity test showed that the data are stationary at the 1%, 5%, and 10% levels of significance. The determined probability (Fstatistic) value of 0.000922 from the ordinary least squares regression is less than the 0.05 significant value, indicating that the data are significantly significant. According to the calculated linear coefficient of determination (R2= 0.825737), the shareholder’s fund and total assets of the chosen enterprises account for 82.5737 percent of the profit after tax. According to the study’s findings, assetliability management and the financial success of insurance businesses in Nigeria are related.